Genetic and Biophysical Models Help Define Marine Conservation Focus Areas - Mertens, Lisa E. A.; Treml, Eric A.; von der Heyden, Sophie (Frontiers in Marine Science, 2018)
Ecological and environmental variables play a major role in the genetic structure of marine populations, but how oceanography affects their dispersal and associated connectivity remains far from being understood. To account for the effect of different dispersal strategies in terms of pelagic larvae and non-pelagic reproduction, we utilize the power of comparative phylogeographic analyses of five phylogenetically and functionally diverse intertidal species along the west coast of South Africa using population genetics and biophysical models within the Benguela Current system. Some broadcast spawners exhibit genetic panmixia, others show genetic structure similar to direct-developing species, suggesting complex recruitment patterns in rocky shore environments. Patterns of genetic structure do not correspond with pelagic larval competency period, with a broadcast spawning urchin displaying the highest levels of population structure. Biophysical models of larval dispersal reveal mixed dispersal patterns, with the strongest connections in a northward direction following the Benguela Current, yet most modelled species also show the capacity for southward (albeit weaker) migration among some sample sites. Some sites, particularly the most northern areas, show very low levels of potential connectivity. Lastly, we synthesized our results to highlight key areas for the development of Marine Protected Areas that capture the evolutionary patterns of marine species of the west coast and find that the results from our molecular and biophysical analyses are coherent with previous suggestions for a network of protected areas.